1967
DOI: 10.1002/ar.1091580410
|View full text |Cite
|
Sign up to set email alerts
|

An autoradiographic study of chondrocyte transformation into chondroclasts and osteocytes during bone formation In vitro

Abstract: Excised mouse pubic bone rudiments were exposed to H"-thymidine. Rudiments preserved immediately after exposure consisted of mesenchyme with a large number of cells showing intense radioactivity. Rudiments incubated on a filter membrane after exposure went through the developmental stages of complete chondrification of the pubic rami followed by periosteal and then endochondral bone formation. Only chondrocytes showed radioactivity in rami consisting of cartilage and periosteal bone that were preserved prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

1968
1968
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(29 citation statements)
references
References 6 publications
0
28
1
Order By: Relevance
“…However, similar experiments performed using rabbit metatarsal cartilage did not result in any radioactively labelled bone cells, even though endochondral ossification started in the grafts (Bentley & Greer 1970). Later, experiments showed that quail growth plate Crelin & Koch (1967) and Holtrop (1966) ª 2015 Japanese Society of Developmental Biologists cartilage, free of perichondrium and periosteum when transplanted into chick chorioallantoic membrane, became transformed into bone and quail osteoblasts and osteocytes were found (Kahn & Simmons 1977). However, whether the chondrocytes directly became osteoblasts or bone cells arose from a resident minor population of osteoblast progenitors could not be excluded.…”
Section: The Fate Of Hypertrophic Chondrocytesmentioning
confidence: 79%
See 1 more Smart Citation
“…However, similar experiments performed using rabbit metatarsal cartilage did not result in any radioactively labelled bone cells, even though endochondral ossification started in the grafts (Bentley & Greer 1970). Later, experiments showed that quail growth plate Crelin & Koch (1967) and Holtrop (1966) ª 2015 Japanese Society of Developmental Biologists cartilage, free of perichondrium and periosteum when transplanted into chick chorioallantoic membrane, became transformed into bone and quail osteoblasts and osteocytes were found (Kahn & Simmons 1977). However, whether the chondrocytes directly became osteoblasts or bone cells arose from a resident minor population of osteoblast progenitors could not be excluded.…”
Section: The Fate Of Hypertrophic Chondrocytesmentioning
confidence: 79%
“…But direct labeling of HCs and lineage tracing are essential for following their fate. Early attempts of pulse-and-chase labeling used autoradiographic methods that labelled dividing chondrocytes from mouse explant rib cartilage (Holtrop 1966) or bone rudiments (Crelin & Koch 1967) exposed to 3 H-thymidine. Both osteoblasts and chondroclasts based on cell morphology became radioactively labelled, suggesting that chondrocytes could convert to other cell types.…”
Section: The Fate Of Hypertrophic Chondrocytesmentioning
confidence: 99%
“…The possibility that HCs are an alternative source of osteoblasts is controversial (12). Support comes from imaging, morphological, and ultrastructural studies in vivo, in which HCs were observed at the chondro-osseous junction and osteoblasts in chondrocyte lacuna (13)(14)(15)(16)(17)(18). Recent lineage studies failed to resolve this issue because non-HC-specific reagents were used to track the fate of HCs (2,19,20) or because the half-life of fluorescent protein tracers in HCs may not be sufficient to span a possible HC-to-osteoblast transition (21).…”
mentioning
confidence: 99%
“…The fate of these cells is not clear, though it has been proposed that following their release from the calcified matrix they use to form multinucleated chondroclasts (17). In mammalian long bone the liberated chondrocytes may be transformed into chondroclasts as well as osteoprogenitor cells which differentiate into osteoblasts and osteocytes (4).…”
Section: Discussionmentioning
confidence: 99%